Modelling a Smart Parking Management System (SPMS) based on integrated IoT - Zainuddin, Ahmad Anwar; Sahak, Rohilah; Jusat, Nuaomi; Kaitane, Wonderful Shammah; Abdul Rahman, Siti Husna; Mohd Mansor, Ahmad Fairuzabadi; Ahmad Puzi, Asmarani; Affendi Yunos, Muhd Farhan; Abd Majid, Mohamed Ibrahim; Hamizan, Hasbullah; Mohd Ramly, Munirah; Subramaniam, Krishnan (Center of Diploma Studies (CeDS), Universiti Tun Hussein Onn Malaysia (UTHM), 2022)
Rapid automobile production and use in recent years has made parking difficult, especially in metropolitan cities. This problem intensifies during busy hours and weekends. Many huge retail complexes have a parking problem. One must search for all parking lanes to park a car. Developing a Smart Parking Management System (SPMS) is the greatest way to help drivers find parking spaces. Internet-of-Things (IoT) has also improved people's lives and society. This work seeks to construct a simple IoT-based Car Parking Management System and create a website that displays parking spot status. Four IR sensors, one servo motor, three red LEDs, and an LCD make up this IoT-based Smart Car Parking System. All these components are connected to NodeMCU ESP8266, the system's controller. NodeMCU handles the process and updates the website with parking availability. Users can easily find available parking spots before heading to the lot. The website allows one-hour advance booking. The status of each parking place is likewise displayed on the entry LCD. This technology solves the city's parking problem and delivers a reliable IoT based parking management system.